2020
DOI: 10.3390/polym12010078
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Intermolecular Interaction and Free Radical Polymerizability of Methacrylates in Supercritical Carbon Dioxide

Abstract: High pressure in situ Fourier transfer infrared/near infrared technology (HP FTIR/NIR) along with theoretical calculation of density functional theory (DFT) method was employed. The solvation behaviors and the free radical homopolymerization of methyl methacrylate (MMA), methacrylate acid (MAA), trifluoromethyl methacrylate (MTFMA) and trifluoromethyl methacrylate acid (TFMAA) in scCO2 were systematically investigated. Interestingly, the previously proposed mechanism of intermolecular-interaction dynamically-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Both the 19 F NMR spectra of SMFA and SCFA (Figure S1b) showed signal peaks associated with −CF 3 at the same chemical shifts (−63 ppm), meaning that the two-step synthesis procedure did not destroy the F atomic groups, and the −CF 3 groups were well preserved after sulfonation and oxidation . As shown in the FT-IR spectra (Figure b), the absorption bands arising from −SO 3 Na were observed in both SMFA (1187, 1096, and 615 cm –1 ) and SCFA (1187, 1079, and 627 cm –1 ), whereas both SMFA and SCFA showed vibration peaks at 731 cm –1 , attributed to −CF 3 . , Peaks at 3168 and 1740 cm –1 were observed in SCFA, corresponding to the stretching vibration of −COOH. The results of NMR and FT-IR confirmed the successful synthesis of SMFA and SCFA.…”
Section: Resultsmentioning
confidence: 90%
“…Both the 19 F NMR spectra of SMFA and SCFA (Figure S1b) showed signal peaks associated with −CF 3 at the same chemical shifts (−63 ppm), meaning that the two-step synthesis procedure did not destroy the F atomic groups, and the −CF 3 groups were well preserved after sulfonation and oxidation . As shown in the FT-IR spectra (Figure b), the absorption bands arising from −SO 3 Na were observed in both SMFA (1187, 1096, and 615 cm –1 ) and SCFA (1187, 1079, and 627 cm –1 ), whereas both SMFA and SCFA showed vibration peaks at 731 cm –1 , attributed to −CF 3 . , Peaks at 3168 and 1740 cm –1 were observed in SCFA, corresponding to the stretching vibration of −COOH. The results of NMR and FT-IR confirmed the successful synthesis of SMFA and SCFA.…”
Section: Resultsmentioning
confidence: 90%
“…This decrease in the sensitivity could arise from various factors. The electron density on the terminal double bond of TFMA ligand is relatively low because of the neighboring electron-withdrawing CF 3 group . Previous studies have shown that introduction of a – CF 3 group at the α position decreases the rate of radical homopolymerization of the TFMA unit. , Different molecular packing of the oxoclusters in Zn­(TFMA) compared to its analogue Zn­(MA)­(TFA) or a reduced ratio of the solubility rates of the unexposed and exposed regions in the developer of choice can also contribute toward this observed decrease in the sensitivity.…”
Section: Resultsmentioning
confidence: 99%